2017
DOI: 10.1176/appi.ajp.2017.17010095
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intrinsic Brain Functional Connectivity in Vulnerability and Resilience to Bipolar Disorder

Abstract: Objective Bipolar disorder is a heritable disorder characterized by mood dysregulation associated with brain functional dysconnectivity. Prior research has focused on the detection of risk- and disease-associated dysconnectivity in individuals with bipolar disorder and their first-degree relatives. The current study seeks to identify adaptive brain connectivity features associated with resilience, defined here as avoidance or delayed illness onset in unaffected siblings of patients with bipolar disorder. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…Because the physiological interpretation of negative correlations is ambiguous (Murphy & Fox, ), functional connections with negative correlation values were not considered here. This approach is widely used in current functional brain network studies of healthy and diseased populations (Bassett, Meyer‐Lindenberg, Achard, Duke, & Bullmore, ; Buckner et al, ; Doucet, Bassett, Yao, Glahn, & Frangou, ; Liang et al, ; Power, Schlaggar, Lessov‐Schlaggar, & Petersen, ; van den Heuvel et al, ). Then, we generated binary functional brain networks by thresholding these correlation matrices with two commonly used thresholding approaches, including a fixed‐density thresholding and a fixed‐correlation thresholding.…”
Section: Methodsmentioning
confidence: 99%
“…Because the physiological interpretation of negative correlations is ambiguous (Murphy & Fox, ), functional connections with negative correlation values were not considered here. This approach is widely used in current functional brain network studies of healthy and diseased populations (Bassett, Meyer‐Lindenberg, Achard, Duke, & Bullmore, ; Buckner et al, ; Doucet, Bassett, Yao, Glahn, & Frangou, ; Liang et al, ; Power, Schlaggar, Lessov‐Schlaggar, & Petersen, ; van den Heuvel et al, ). Then, we generated binary functional brain networks by thresholding these correlation matrices with two commonly used thresholding approaches, including a fixed‐density thresholding and a fixed‐correlation thresholding.…”
Section: Methodsmentioning
confidence: 99%
“…However, closer inspection of previous case-control neuroimaging studies suggests that the somatomotor regions are often reported, but not emphasized within prevailing models of psychiatry. For example, altered RSFC within the somatomotor network (54)(55)(56), as well as between the somatomotor networks and thalamus have been documented in case-control studies investigating SZ, SZAD and BD patients (54,(57)(58)(59)(60)(61)(62)(63). Altered thalamosomatomotor FC has also been linked to SZ symptom severity (54,57,58).…”
Section: Somatomotor Network Are Transdiagnostic Hubsmentioning
confidence: 98%
“…Abnormalities in resting-state (task-free, intrinsic) functional connectivity (rsFC) have also been found in individuals at familial risk for BD [14][15][16][17][18][19], and again, the IFG and VLPFC emerge as key regions that distinguish at-risk and healthy controls [14,15] (Table S1). In healthy, young offspring of a bipolar parent (vs. healthy controls), Singh and co-authors [14] found less VLPFCcaudate rsFC and more rsFC within the VLPFC, although the latter was associated with higher functioning [15].…”
Section: Introductionmentioning
confidence: 95%